Modified ferromanganese ammonium phosphate, modified ferromanganese pyrophosphate and preparation method and application of modified ferromanganese ammonium phosphate and modified ferromanganese pyrophosphate
Modified ammonium manganese phosphate was prepared by ion exchange method and modified ferromanganese pyrophosphate and lithium manganese phosphate were prepared by sintering, which solved the problem that doped ferromanganese pyrophosphate easily introduced anionic impurities in the prior art, and significantly improved the electrochemical performance of the battery.
Patent Information
- Application Number
- CN202411993554.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-11
AI Technical Summary
The prior art is prone to introduce too many anionic impurities when preparing doped ferromanganese pyrophosphate, which affects the electrochemical performance of lithium manganese ferromanganese phosphate positive electrode materials.
Modified ferromantetraphosphate was prepared by ion exchange method. By controlling the reaction conditions and selecting low-impact ferromantetraphosphate as templates, the introduction of anionic impurities was avoided, and modified ferromantetraphosphate and lithium mangantetraphosphate were prepared by sintering.
The introduction of anionic impurities is effectively avoided, the sulfur content in modified ferroferrophosphate is reduced, the electrochemical performance of metal-doped lithium manganese phosphate prepared is improved, and the capacity, rate performance and cycle stability of the battery are significantly improved.
Smart Images

Figure CN119591077A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and more specifically, relates to a modified ammonium ferric manganese phosphate, a modified ferromanganese pyrophosphate, and a preparation method and application thereof. Background Art
[0002] As a solid solution of iron pyrophosphate and manganese pyrophosphate, manganese, iron and phosphorus elements in pyrophosphate manganese can be evenly distributed at the atomic level in the bulk phase, making it an effective precursor for synthesizing high-performance lithium iron manganese phosphate. Compared with precursors such as ammonium manganese ferric phosphate, ferromanganese phosphate, ferromanganese carbonate, and ferromanganese oxalate, the pyrophosphate manganese precursor prepared by the sintering process can effectively remove the hydrophilic groups on the surface of the conventional ferromanganese phosphate precursor to avoid high agglomeration of the precursor during the grinding process, thereby reducing the grinding efficiency and accuracy; the selection of pyrophosphate manganese precursor can avoid the generation of large amounts of water vapor, carbon dioxide, ammonia and other gases during the subsequent sintering process. These gases make the structure of the lithium iron manganese phosphate material loose and increase the bulk defects, which is not conducive to the stability of the material structure and the improvement of the material energy density. In addition, during the charge and discharge process, the manganese iron phosphate lithium ion material is converted from Mn 3+ The Jahn-Teller effect and manganese dissolution caused by this phenomenon make the cycle stability and rate performance of lithium iron manganese phosphate poor, which can be improved by metal cation doping. Compared with the preparation technology of lithium iron manganese phosphate that adds metal dopants in the grinding process, pre-doping with metal elements in the pyrophosphate iron manganese phase can make each element evenly distributed at the atomic level in the pyrophosphate iron manganese / lithium iron manganese phosphate lattice, extend the Li-O bond length and accelerate the migration of lithium ions, and effectively avoid doping metal elements occupying Li sites or introducing too many Li site defects to reduce the material structure stability and lithium ion migration rate.
[0003] At present, the technology for preparing doped manganese iron pyrophosphate is mainly obtained by sintering ammonium manganese iron phosphate. In the prior art, metal-doped ammonium manganese iron phosphate is mainly prepared by co-precipitation, in which phosphate, manganese salt, iron salt and doped metal salt are co-precipitated under appropriate pH and temperature conditions to generate metal-doped ammonium manganese iron phosphate, which easily introduces too many anion impurities, thereby affecting the electrochemical performance of lithium manganese iron phosphate positive electrode materials. Summary of the invention
[0004] In order to solve the problems existing in the prior art, the primary purpose of the present invention is to provide a method for preparing modified ammonium manganese ferric phosphate.
[0005] Another object of the present invention is to provide a modified ammonium manganese ferric phosphate.
[0006] Another object of the present invention is to provide a modified ferromanganese pyrophosphate.
[0007] Another object of the present invention is to provide a modified lithium manganese iron phosphate.
[0008] Another object of the present invention is to provide a battery.
[0009] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0010] A method for preparing modified ammonium manganese ferric phosphate comprises the following steps:
[0011] S1. The iron substance is placed in phosphoric acid for reaction, an oxidant is added for reaction, and an alkaline pH regulator containing nitrogen is added to obtain a first system containing ammonium iron phosphate;
[0012] S2. Mix manganese sulfate and a doped metal salt, add the mixture to the first system, control the pH value of the system to be 7 to 8.5, and react under an inert atmosphere to obtain the modified ammonium manganese ferric phosphate.
[0013] The present invention adopts an ion exchange method to prepare modified ammonium manganese iron phosphate. The ion exchange method can make manganese, iron and doped metal atoms evenly distributed at the atomic level in the precursor lattice, effectively avoiding the generation of other metal impurities. The ratio of the total molar amount of manganese, iron and doped metal in the metal-doped ammonium manganese iron phosphate obtained by the reaction to the molar amount of phosphorus is less than 1. At the same time, low-impurity ammonium ferric phosphate is used as a template for ion exchange. The prepared metal-doped ammonium manganese iron phosphate can effectively avoid the introduction of anionic impurities (sulfate), greatly reducing the sulfur content in the modified ammonium manganese iron phosphate, thereby improving the electrochemical performance of the metal-doped lithium manganese iron phosphate prepared thereby.
[0014] The present invention uses a single iron substance to react with phosphoric acid to form ferrous dihydrogen phosphate, then adds an oxidant to oxidize it into ferric phosphate, and performs an ion exchange reaction with a manganese salt and a doped metal salt through mechanisms such as pH regulation, adsorption, and complexation to exchange the iron element in the ammonium ferric phosphate, thereby forming metal-doped ammonium manganese ferric phosphate. Since ferrous dihydrogen phosphate is oxidized to ferric phosphate to produce phosphate radicals, the exchanged iron ions continue to complex with the manganese ions, doped metal ions, and phosphate radicals in the system to react to form metal-doped ammonium manganese ferric phosphate.
[0015] In the present invention, before the mixture of manganese sulfate and doped metal salt is added to the first system, the pH value needs to be controlled to be 7 to 8.5. After the mixture of manganese sulfate and doped metal salt is added to the first system, the pH value of the system decreases, which may be due to the presence of a buffer system in the first system. When the pH value of the system is controlled again, it recovers slowly.
[0016] Specifically, the chemical formula of the modified ammonium manganese ferric phosphate is NH4Mn x Fe 1-x-m M m PO4, wherein 0<x<1, 0<m<0.1, and M is a doping metal.
[0017] Preferably, 0.2<x<0.8, 0<m<0.1.
[0018] More preferably, 0.5≤x≤0.7, 0.03≤m≤0.09.
[0019] In the present invention, selecting metal doping within the above range is conducive to forming place-occupying doping of doped metal elements on the manganese / iron sites in ammonium manganese iron phosphate, avoiding the introduction of disordered lithium doping or lithium site defects that affect the electrochemical properties of the material.
[0020] Specifically, the molar ratio of Fe to P in step S1 is 1:(2-4).
[0021] Controlling the molar ratio of Fe and P in the reaction system within this range is beneficial to regulating the ratio of metal to P in the modified ammonium manganese iron phosphate precursor to be less than 1, so that defect sites of Fe / Mn metal are constructed in situ inside the precursor, thereby accelerating lithium ion migration and enhancing structural stability.
[0022] Specifically, the pH adjuster is one of ammonia water, urea or ammonium carbonate.
[0023] The pH regulator in the present invention is required to be alkaline, be able to generate ammonium ions with phosphoric acid, and not introduce other impurity ions.
[0024] Specifically, in step S1, the reaction time of elemental iron and phosphoric acid is 0.5 to 10 hours.
[0025] Specifically, after the oxidant is added in step S1, the reaction temperature is 50-85° C., and the reaction time is 0.5-6 h.
[0026] Specifically, the metal element in the doped metal salt includes at least one of Ca, Mg, Al, Ti, V, Co, Ni, Cr, Zn, Sn, Mo, Cu, Zr, Nb, Ta, Y, Ce, W, Sc or Ga.
[0027] The present invention adopts the above-mentioned metal elements to dope and modify the ammonium manganese iron phosphate, which is beneficial to realize the regulation of the electronic structure from the inside of the lattice and avoid the prepared lithium manganese iron phosphate Mn during the charge and discharge process. 3+ The Jahn-Teller effect and manganese dissolution phenomenon caused by the reaction can improve the conductivity, cycle stability and rate performance of lithium manganese iron phosphate.
[0028] Specifically, the doping metal salt may be at least one of sulfate, nitrate, acetate, ammonium salt or chloride salt of the corresponding metal ion.
[0029] Specifically, the reaction temperature in step S2 is 50-90°C.
[0030] Specifically, the reaction time in step S2 is 0.5 to 10 hours.
[0031] Specifically, the pH adjuster is at least one of ammonia water, urea or ammonium carbonate.
[0032] In a specific embodiment, the oxidant is one of hydrogen peroxide, oxygen and ozone.
[0033] The present invention also protects the modified ammonium manganese ferric phosphate prepared by the above preparation method.
[0034] The ratio of the total molar number of manganese, iron and doped metal to the molar number of P in the modified ammonium manganese ferric phosphate prepared by the above preparation method is less than 1.
[0035] The present invention also protects a modified ferromanganese pyrophosphate, which is prepared by calcining the modified ammonium ferromanganese phosphate in an inert atmosphere.
[0036] Specifically, the calcination is to increase the temperature to 400-800° C. at a heating rate of 1-10° C. / min and keep the temperature for 1-6 hours.
[0037] The present invention also protects a modified lithium manganese iron phosphate, which is prepared from the modified manganese iron pyrophosphate.
[0038] Specifically, the preparation method of lithium manganese iron phosphate includes the following steps:
[0039] The modified manganese iron pyrophosphate, a lithium source and a carbon source are dispersed in a solvent, sand-milled, spray-dried, and then sintered in an inert atmosphere to obtain the manganese iron lithium phosphate.
[0040] Specifically, the lithium source is any one or more types of positive electrode active materials known in the art, for example, at least one of lithium carbonate, lithium hydroxide, and lithium acetate.
[0041] Specifically, the carbon source is any one or more carbon sources known in the art for preparing positive electrode active materials, for example, it can be at least one of glucose, sucrose, starch, cellulose, polyethylene glycol, fructose, ascorbic acid, polyvinyl pyrrolidone, and polyvinylidene fluoride.
[0042] Specifically, the solvent is water and / or ethanol.
[0043] Specifically, the sintering is to increase the temperature to 600-800° C. at a heating rate of 1-10° C. / min and keep the temperature for 5-14 hours.
[0044] The present invention also provides a battery comprising the modified lithium manganese iron phosphate.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] The present invention provides a method for preparing modified ammonium manganese iron phosphate, wherein a metal-doped modified ammonium manganese iron phosphate precursor is prepared by an ion exchange method, and metal-doped modified ferromanganese pyrophosphate is prepared by sintering, and then metal-doped modified lithium manganese iron phosphate is prepared. Mn, Fe and doped metal elements in the metal-doped modified ammonium manganese iron phosphate and ferromanganese pyrophosphate synthesized by the method are uniformly distributed at the atomic level in the lattice of the lithium manganese iron phosphate precursor, forming a single-phase solid solution of ammonium manganese iron phosphate or ferromanganese pyrophosphate, and the ratio of the total molar number of Mn, Fe and doped metal elements in the ammonium manganese iron phosphate to the molar number of P is less than 1, so that the prepared lithium manganese iron phosphate has a larger lithium ion migration path and space, accelerates the migration rate of lithium ions, and improves the stability of the material structure.
[0047] The present invention uses low-impurity ammonium iron phosphate as a template for ion exchange, and the prepared metal-doped ammonium manganese iron phosphate can effectively avoid the introduction of anionic impurities (sulfate). For the modified lithium manganese iron phosphate prepared using a metal sulfate salt, the preparation method of the present invention can control the sulfur impurity content in the precursor, which avoids the secondary desulfurization process, so that the sulfur impurity content (≤10ppm) in the modified lithium manganese iron phosphate reaches the battery level, thereby improving the electrochemical performance of the modified lithium manganese iron phosphate positive electrode material in the battery.
[0048] The modified ammonium manganese iron phosphate prepared by the present invention is sintered to obtain pyromanganese iron phosphate, which is mixed with a lithium source and a carbon source and then sintered to obtain lithium manganese iron phosphate with a high compaction density (reaching 2.3 g / cm 3 It has good electrical conductivity and small powder resistance. When applied to lithium-ion batteries, the battery capacity, rate performance and cycle stability can be significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 NH4Mn obtained in Example 1 of the present invention 0.5 Fe 0.47 Mg 0.01 Ti 0.01 Cu 0.01 Scanning electron microscopy characterization of PO4 precursor. DETAILED DESCRIPTION
[0050] The content of the present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present embodiment are conventional reagents, methods and equipment in the art.
[0051] Example 1
[0052] 1. A modified ammonium manganese ferric phosphate NH4Mn 0.5 Fe 0.47 Mg 0.01 Ti 0.01 Cu 0.01 The preparation method of PO4 precursor is as follows:
[0053] Under nitrogen atmosphere and reaction temperature of 50°C, 0.766 kg of iron block was placed in a high-efficiency sealed synthesis reactor and 19.166 kg of ultrapure water was slowly pumped in as a base liquid after slurrying, and then 3.356 kg of 85 wt% concentrated phosphoric acid solution was pumped in at 60 r / min using a 16# pipe; after the phosphoric acid solution was completely pumped in, the reactor system was stirred at 700 r / min for 4 hours until the iron block was completely dissolved to prepare a ferrous dihydrogen phosphate solution A with an iron content of 3.29%;
[0054] Under nitrogen atmosphere and room temperature, 2.46 kg of manganese sulfate monohydrate, 35.039 g of anhydrous magnesium sulfate, 85.564 g of ammonium titanium oxalate, and 36.333 g of copper sulfate pentahydrate were dissolved in ultrapure water in a molar ratio of 50:1:1:1 among the metal elements manganese, magnesium, titanium, and copper to prepare a 3 mol / L metal salt mixed solution B;
[0055] In a nitrogen atmosphere, the reaction temperature was controlled to 72°C, and the above solution A was used as the base liquid. 1.804kg of 27.5wt% hydrogen peroxide solution was pumped in at 60r / min using a 16# tube; after the hydrogen peroxide solution was completely pumped in, the mixture was stirred and reacted for 15min, and then 0.323kg of 27.5wt% hydrogen peroxide solution was pumped in at the same speed to ensure that the ferrous dihydrogen phosphate in the system was fully reacted to ferric phosphate. In a nitrogen atmosphere, the temperature of the above system was controlled to 72°C and fully reacted for 1.5h, and then ammonia water was pumped into the system at 100r / min to adjust the pH of the system to 7.
[0056] Subsequently, the prepared metal salt mixed solution B was pumped into the system at a speed of 100 r / min, and after the pH of the system was adjusted to 7 with ammonia water, the system was kept at a constant temperature of 72° C. for 4 hours under a nitrogen atmosphere to obtain a hydrated ammonium manganese iron phosphate slurry. The prepared hydrated ammonium manganese iron phosphate slurry was filtered and washed with a vertical filter press until the conductivity of the washing water was 188 μS / cm, and then the filter cake was flash evaporated to obtain the modified ammonium manganese iron phosphate precursor.
[0057] 2. Lithium iron manganese phosphate LiMn 0.5 Fe 0.47 Mg 0.01 Ti 0.01 Cu 0.01 The preparation method of PO4 is as follows:
[0058] The NH4Mn 0.5 Fe 0.47 Mg 0.01 Ti 0.01 Cu 0.01 The PO4 precursor was placed in a graphite crucible in a nitrogen atmosphere box furnace (oxygen content less than 10 ppm), and the temperature was raised to 500°C at a heating rate of 5°C / min and kept at this temperature for 3 h to prepare a metal cation-doped modified manganese iron pyrophosphate intermediate (Mn 0.5 Fe 0.47 Mg 0.01 Ti 0.01 Cu 0.01 )2P2O7. Subsequently, glucose, lithium carbonate, lithium dihydrogen phosphate, and modified pyrophosphate manganese iron were added according to the molar ratio of Li:P:(Mn+Fe+Mg+Ti+Cu) of 1.08:1.02:1, and the mass of glucose was 5wt% of the mass of modified pyrophosphate manganese iron, and dispersed in ultrapure water to obtain a slurry with a solid content of 40%, and the slurry was ground in a sand mill to a particle size of D 50 When the particle size is 0.32 μm, the slurry is treated with a spray granulation dryer to obtain a spray powder. The spray powder is then placed in a graphite sagger in a nitrogen atmosphere box furnace (oxygen content is less than 10 ppm), and the temperature is raised to 680°C at a heating rate of 5°C / min for 9 hours. After the box furnace temperature naturally drops to room temperature, the sintered powder is air flow crushed and sieved to obtain a particle size D 50 It is a 1.12μm lithium manganese iron phosphate positive electrode material.
[0059] Example 2
[0060] 1. A modified ammonium manganese ferric phosphate NH4Mn 0.6 Fe 0.31 Mg 0.04 Ti 0.03 Al 0.01 Co 0.01 The preparation method of PO4 precursor is as follows:
[0061] Under nitrogen atmosphere and reaction temperature of 45°C, 0.766 kg of iron block was placed in a high-efficiency sealed synthesis reactor and 17.434 kg of ultrapure water was slowly pumped in as a base liquid after slurrying, and then 5.088 kg of 85 wt% concentrated phosphoric acid solution was pumped in at 60 r / min using a 16# pipe; after the phosphoric acid solution was completely pumped in, the reactor system was stirred at 700 r / min for 4 hours until the iron block was completely dissolved to prepare a ferrous dihydrogen phosphate solution A with an iron content of 3.29%;
[0062] Under nitrogen atmosphere and room temperature, 4.476 kg of manganese sulfate monohydrate, 212.446 g of anhydrous magnesium sulfate, 365.297 g of ammonium oxytitanium oxalate, 75.503 g of aluminum sulfate, and 124.063 g of cobalt sulfate heptahydrate were dissolved in ultrapure water according to the molar ratio of metal elements manganese, magnesium, titanium, aluminum, and cobalt of 60:4:3:1:1 to prepare a 3 mol / L metal salt mixed solution B;
[0063] In a nitrogen atmosphere, the reaction temperature was controlled to 76°C, and the above solution A was used as the base liquid. 2.735kg of 27.5wt% hydrogen peroxide solution was pumped in at 60r / min using a 16# tube; after the hydrogen peroxide solution was completely pumped in, it was stirred and reacted for 15min, and then 0.49kg of 27.5wt% hydrogen peroxide solution was pumped in at the same speed to ensure that the ferrous dihydrogen phosphate in the system was fully reacted to ferric phosphate. In a nitrogen atmosphere, the temperature of the above system was controlled to 76°C and fully reacted for 1.5h, and then ammonia water was pumped into the system at a speed of 100r / min to adjust the pH of the system to 7.4.
[0064] Subsequently, the prepared metal salt mixed solution B was pumped into the system at a speed of 100 r / min, and after the pH of the system was adjusted to 7.4 with ammonia water, the system was kept at a constant temperature of 76° C. for 4 hours under a nitrogen atmosphere to obtain a hydrated ammonium manganese iron phosphate slurry. The prepared hydrated ammonium manganese iron phosphate slurry was filtered and washed with a vertical filter press until the conductivity of the washing water was 156 μS / cm, and then the filter cake was flash evaporated to obtain a modified ammonium manganese iron phosphate precursor.
[0065] 2. Lithium iron manganese phosphate LiMn 0.6 Fe 0.31 Mg 0.04 Ti 0.03 Al 0.01 Co 0.01 The preparation method of PO4 is as follows:
[0066] The NH4Mn 0.6 Fe 0.31 Mg 0.04 Ti 0.03 Al 0.01 Co 0.01 The PO4 precursor was placed in a graphite crucible in a nitrogen atmosphere box furnace (oxygen content less than 10 ppm), and the temperature was raised to 600°C at a heating rate of 8°C / min and kept at this temperature for 3 h to prepare a metal cation-doped modified manganese iron pyrophosphate intermediate (Mn 0.6 Fe 0.31 Mg 0.04 Ti 0.03 Al 0.01 Co 0.01)2P2O7. Subsequently, sucrose, lithium carbonate, lithium dihydrogen phosphate, and modified pyrophosphate manganese iron were added according to the molar ratio of Li:P:(Mn+Fe+Mg+Ti+Al+Co) of 1.05:1.01:1, and the mass of sucrose was 4.8wt% of the mass of modified pyrophosphate manganese iron, and dispersed in ultrapure water to obtain a slurry with a solid content of 38%, and the slurry was ground in a sand mill to a particle size of D 50 When the particle size is 0.31 μm, the slurry is treated with a spray granulation dryer to obtain a spray powder. The spray powder is then placed in a graphite sagger in a nitrogen atmosphere box furnace (oxygen content is less than 10 ppm), and the temperature is raised to 700°C at a heating rate of 2°C / min and kept for 9 hours. After the box furnace temperature naturally drops to room temperature, the sintered powder is air flow crushed and sieved to obtain a particle size D 50 It is a 1.08μm lithium manganese iron phosphate positive electrode material.
[0067] Example 3
[0068] 1. A modified ammonium manganese ferric phosphate NH4Mn 0.7 Fe 0.26 Mg 0.02 Co 0.02 The preparation method of PO4 precursor is as follows:
[0069] Under nitrogen atmosphere and reaction temperature of 55°C, 0.766 kg of iron block was placed in a high-efficiency sealed synthesis reactor and 16.455 kg of ultrapure water was slowly pumped in as a base liquid after slurrying, and then 6.067 kg of 85 wt% concentrated phosphoric acid solution was pumped in at 60 r / min using a 16# pipe; after the phosphoric acid solution was completely pumped in, the reactor system was stirred at 700 r / min for 4 hours until the iron block was completely dissolved to prepare ferrous dihydrogen phosphate solution A with an iron content of 3.29%;
[0070] Under nitrogen atmosphere and room temperature, 6.226 kg of manganese sulfate monohydrate, 126.651 g of anhydrous magnesium sulfate, and 295.776 g of cobalt sulfate heptahydrate were dissolved in ultrapure water in a molar ratio of 35:1:1 among the metal elements manganese, magnesium, and cobalt to prepare a 3 mol / L metal salt mixed solution B;
[0071] In a nitrogen atmosphere, the reaction temperature was controlled to 76°C, and the above solution A was used as the base liquid. 3.252kg of 27.5wt% hydrogen peroxide solution was pumped in at 60r / min using a 16# tube; after the hydrogen peroxide solution was completely pumped in, it was stirred and reacted for 15min, and then 0.76kg of 27.5wt% hydrogen peroxide solution was pumped in at the same speed to ensure that the ferrous dihydrogen phosphate in the system was fully reacted to ferric phosphate. In a nitrogen atmosphere, the temperature of the above system was controlled to 76°C and fully reacted for 1.5h, and then ammonia water was pumped into the system at a speed of 100r / min to adjust the pH of the system to 7.8.
[0072] Subsequently, the prepared metal salt mixed solution B was pumped into the system at a speed of 100 r / min, and after the pH of the system was adjusted to 7.8 with ammonia water, the system was kept at a constant temperature of 76° C. for 4 hours under a nitrogen atmosphere to obtain a hydrated ammonium manganese iron phosphate slurry. The prepared hydrated ammonium manganese iron phosphate slurry was filtered and washed with a vertical filter press until the conductivity of the washing water was 162 μS / cm, and then the filter cake was flash evaporated to obtain a modified ammonium manganese iron phosphate precursor.
[0073] 2. Lithium iron manganese phosphate LiMn 0.7 Fe 0.26 Mg 0.02 Co 0.02 The preparation method of PO4 is as follows:
[0074] NH4Mn 0.7 Fe 0.26 Mg 0.02 Co 0.02 The PO4 precursor was placed in a graphite crucible in a nitrogen atmosphere box furnace (oxygen content less than 10 ppm), and the temperature was raised to 600°C at a heating rate of 8°C / min and kept at this temperature for 3 h to prepare a metal cation-doped modified manganese iron pyrophosphate intermediate (Mn 0.7 Fe 0.26 Mg 0.02 Co 0.02 )2P2O7. Then, polyethylene glycol, lithium carbonate, lithium dihydrogen phosphate, and modified pyrophosphate manganese iron were added according to the molar ratio of Li:P:(Mn+Fe+Mg+Co) of 1.06:1.03:1, and the mass of polyethylene glycol was 5.2wt% of the mass of modified pyrophosphate manganese iron, and dispersed in ultrapure water to obtain a slurry with a solid content of 35%, and the slurry was ground in a sand mill to a particle size of D 50 When the particle size is 0.35 μm, the slurry is treated with a spray granulation dryer to obtain a spray powder. The spray powder is then placed in a graphite sagger in a nitrogen atmosphere box furnace (oxygen content is less than 10 ppm), and the temperature is raised to 720°C at a heating rate of 4°C / min and kept for 10 hours. After the box furnace temperature naturally drops to room temperature, the sintered powder is air flow crushed and sieved to obtain a particle size D50 It is a 1.15μm lithium manganese iron phosphate positive electrode material.
[0075] Comparative Example 1
[0076] 1. Lithium iron manganese phosphate LiMn 0.5 Fe 0.47 Mg 0.01 Ti 0.01 Cu 0.01 The preparation method of PO4 is as follows:
[0077] Glucose, lithium carbonate, lithium dihydrogen phosphate, ferrous sulfate heptahydrate, manganese sulfate monohydrate, anhydrous magnesium sulfate, ammonium oxytitanium oxalate, and copper sulfate pentahydrate were added according to the molar ratio of Li:P:Mn:Fe:Mg:Ti:Cu of 1.08:1.02:0.5:0.47:0.01:0.01:0.01, and the mass of glucose was the same as that in Example 1. The material was added and dispersed in ultrapure water to obtain a slurry with a solid content of 40%, and the slurry was ground to a particle size D in a sand mill. 50 When the particle size is 0.32 μm, the slurry is treated with a spray granulation dryer to obtain a spray powder. The spray powder is then placed in a graphite sagger in a nitrogen atmosphere box furnace (oxygen content is less than 10 ppm), and the temperature is raised to 680°C at a heating rate of 5°C / min for 9 hours. After the box furnace temperature naturally drops to room temperature, the sintered powder is air flow crushed and sieved to obtain a particle size D 50 The modified lithium manganese iron phosphate positive electrode material is 1.52μm.
[0078] Comparative Example 2
[0079] 1. A modified ammonium manganese ferrous phosphate precursor NH4Mn 0.5 Fe 0.47 Mg 0.01 Ti 0.01 Cu 0.01 The preparation method of PO4 is as follows:
[0080] Ammonium dihydrogen phosphate, ferrous sulfate heptahydrate, manganese sulfate monohydrate, anhydrous magnesium sulfate, ammonium oxalyl titanate, and copper sulfate pentahydrate are mixed in ultrapure water according to the molar ratio of P:Mn:Fe:Mg:Ti:Cu of 1.02:0.5:0.47:0.01:0.01:0.01, and in a nitrogen protective atmosphere, after the pH of the system is adjusted to 7 by ammonia water, the reaction temperature is controlled to 72°C for coprecipitation reaction to obtain hydrated ammonium manganese iron phosphate slurry. The prepared hydrated ammonium manganese iron phosphate slurry is filtered and washed with a vertical filter press until the conductivity of the washing water is 188μS / cm, and then the filter cake is flash evaporated to obtain the modified ammonium manganese iron phosphate precursor.
[0081] 2. Lithium iron manganese phosphate LiMn 0.5 Fe0.47 Mg 0.01 Ti 0.01 Cu 0.01 The preparation method of PO4 is as follows:
[0082] The NH4Mn 0.5 Fe 0.47 Mg 0.01 Ti 0.01 Cu 0.01 The PO4 precursor was placed in a graphite crucible and placed in a nitrogen atmosphere box furnace (oxygen content less than 10 ppm), and the temperature was raised to 500°C at a heating rate of 5°C / min and kept for 3 hours to prepare modified pyrophosphate manganese iron doped with metal cations. Subsequently, glucose, lithium carbonate, lithium dihydrogen phosphate, and modified pyrophosphate manganese iron were added according to the molar ratio of Li:P:(Mn+Fe+Mg+Ti+Cu) of 1.08:1.02:1, and the mass of glucose was 5wt% of the mass of modified pyrophosphate manganese iron, and dispersed in ultrapure water to obtain a slurry with a solid content of 40%, and the slurry was ground in a sand mill to a particle size of D 50 When the particle size is 0.32 μm, the slurry is treated with a spray granulation dryer to obtain a spray powder. The spray powder is then placed in a graphite sagger in a nitrogen atmosphere box furnace (oxygen content is less than 10 ppm), and the temperature is raised to 680°C at a heating rate of 5°C / min for 9 hours. After the box furnace temperature naturally drops to room temperature, the sintered powder is air flow crushed and sieved to obtain a particle size D 50 It is a lithium manganese iron phosphate positive electrode material with a particle size of 1.47 μm.
[0083] Comparative Example 3
[0084] 1. NH4Mn 0.5 Fe 0.47 Mg 0.01 Ti 0.01 Cu 0.01 Preparation of PO4 precursor
[0085] Under nitrogen atmosphere and reaction temperature of 50°C, 0.766 kg of iron block was placed in a high-efficiency sealed synthesis reactor and 19.166 kg of ultrapure water was slowly pumped in as a base liquid after slurrying, and then 3.356 kg of 85 wt% concentrated phosphoric acid solution was pumped in at 60 r / min using a 16# pipe; after the phosphoric acid solution was completely pumped in, the reactor system was stirred at 700 r / min for 4 hours until the iron block was completely dissolved to prepare a ferrous dihydrogen phosphate solution A with an iron content of 3.29%;
[0086] Under nitrogen atmosphere and room temperature, 2.46 kg of manganese sulfate monohydrate, 35.039 g of anhydrous magnesium sulfate, 85.564 g of ammonium titanium oxalate, and 36.333 g of copper sulfate pentahydrate were dissolved in ultrapure water in a molar ratio of 50:1:1:1 among the metal elements manganese, magnesium, titanium, and copper to prepare a 3 mol / L metal salt mixed solution B;
[0087] In a nitrogen atmosphere, the reaction temperature was controlled to 72°C, and the above solution A was used as the base liquid. 1.804kg of 27.5wt% hydrogen peroxide solution was pumped in at 60r / min using a 16# tube; after the hydrogen peroxide solution was completely pumped in, the mixture was stirred and reacted for 15min, and then 0.323kg of 27.5wt% hydrogen peroxide solution was pumped in at the same speed to ensure that the ferrous dihydrogen phosphate in the system was fully reacted to ferric phosphate. In a nitrogen atmosphere, the temperature of the above system was controlled to 72°C and fully reacted for 1.5h, and then ammonia water was pumped into the system at 100r / min to adjust the pH of the system to 7.
[0088] Subsequently, the prepared metal salt mixed solution B was pumped into the system at a speed of 100 r / min, and after the pH of the system was adjusted to 7 with ammonia water, the system was kept at a constant temperature of 72° C. for 4 hours under a nitrogen atmosphere to obtain a hydrated ammonium manganese iron phosphate slurry. The prepared hydrated ammonium manganese iron phosphate slurry was filtered and washed with a vertical filter press until the conductivity of the washing water was 188 μS / cm, and then the filter cake was flash evaporated to obtain a hydrated ammonium manganese iron phosphate precursor.
[0089] 2.LiMn 0.5 Fe 0.47 Mg 0.01 Ti 0.01 Cu 0.01 Preparation of PO4
[0090] Subsequently, glucose, lithium carbonate, lithium dihydrogen phosphate, modified NH4Mn 0.5 Fe 0.47 Mg 0.01 Ti 0.01 Cu 0.01 The PO4 precursor is prepared according to the ratio of Li:P:(Mn+Fe+Mg+Ti+Cu) of 1.08:1.02:1. The mass of glucose is the same as that in Example 1. It is added and dispersed in ultrapure water to obtain a slurry with a solid content of 40%. The slurry is then ground in a sand mill to a particle size of D 50 When the particle size is 0.32 μm, the slurry is treated with a spray granulation dryer to obtain a spray powder. The spray powder is then placed in a graphite sagger in a nitrogen atmosphere box furnace (oxygen content is less than 10 ppm), and the temperature is raised to 680°C at a heating rate of 5°C / min for 9 hours. After the box furnace temperature naturally drops to room temperature, the sintered powder is air flow crushed and sieved to obtain a particle size D50 The modified lithium manganese iron phosphate positive electrode material is 1.68μm.
[0091] Comparative Example 4
[0092] 1. Preparation of NH4FePO4 precursor
[0093] Under nitrogen atmosphere and reaction temperature of 50°C, 0.766 kg of iron block was placed in a high-efficiency sealed synthesis reactor and 18.578 kg of ultrapure water was slowly pumped in as a base liquid after slurrying, and then 3.154 kg of 85 wt% concentrated phosphoric acid solution was pumped in at 60 r / min using a 16# pipe; after the phosphoric acid solution was completely pumped in, the reactor system was stirred at 700 r / min for 4 hours until the iron block was completely dissolved to prepare ferrous dihydrogen phosphate solution A;
[0094] In a nitrogen atmosphere, the reaction temperature is controlled to 72°C, and the above solution A is used as the base liquid. 0.846kg of 27.5wt% hydrogen peroxide solution is pumped in at a speed of 60r / min using a 16# tube; after the hydrogen peroxide solution is completely pumped in, it is stirred and reacted for 15min, and then 0.38kg of 27.5wt% hydrogen peroxide solution is pumped in at the same speed to ensure that the ferrous dihydrogen phosphate in the system is fully reacted to ferric phosphate. Under a nitrogen atmosphere, the temperature of the above system is controlled to 72°C for full reaction for 1.5h, and then ammonia water is pumped into the system at a speed of 100r / min to adjust the pH of the system to 7. Use a vertical filter press to filter the prepared hydrated ammonium ferric phosphate slurry, wash it until the conductivity of the wash water is 291μS / cm, and then flash evaporate the filter cake to obtain a hydrated ammonium ferric phosphate precursor.
[0095] 2.LiMn 0.5 Fe 0.47 Mg 0.01 Ti 0.01 Cu 0.01 Preparation of PO4
[0096] Subsequently, glucose, lithium carbonate, lithium dihydrogen phosphate, NH4FePO4 precursor, manganese sulfate monohydrate, anhydrous magnesium sulfate, ammonium oxytitanium oxalate, and copper sulfate pentahydrate were added and dispersed in ultrapure water according to the molar ratio of Li:P:Mn:Fe:Mg:Ti:Cu of 1.08:1.02:0.5:0.47:0.01:0.01:0.01, and the mass of glucose was the same as that in Example 1 to obtain a slurry with a solid content of 40%, and the slurry was ground in a sand mill to a particle size D 50When the particle size is 0.32 μm, the slurry is treated with a spray granulation dryer to obtain a spray powder. The spray powder is then placed in a graphite sagger in a nitrogen atmosphere box furnace (oxygen content is less than 10 ppm), and the temperature is raised to 680°C at a heating rate of 5°C / min for 9 hours. After the box furnace temperature naturally drops to room temperature, the sintered powder is air flow crushed and sieved to obtain a particle size D 50 The modified lithium manganese iron phosphate positive electrode material is 1.45μm.
[0097] Performance Testing
[0098] The NH4Mn obtained in Example 1 0.5 Fe 0.47 Mg 0.01 Ti 0.01 Cu 0.01 The micromorphology of the PO4 precursor was analyzed by scanning electron microscopy. Figure 1 As shown. Figure 1 It can be seen that the prepared NH4Mn 0.5 Fe 0.47 Mg 0.01 Ti 0.01 Cu 0.01 The PO4 precursor is composed of nanosheets and micron-shaped uniform particles, which is conducive to efficient grinding to the target particle size, which shows that NH4Mn 0.5 Fe 0.47 Mg 0.01 Ti 0.01 Cu 0.01 Homogeneous synthesis of PO4 precursors.
[0099] The element contents of the modified ammonium manganese iron phosphate, manganese iron pyrophosphate and lithium manganese iron phosphate prepared in the examples and comparative examples were detected by ICP-OES. The element analysis results are shown in Table 1.
[0100] The particle size of the lithium iron manganese phosphate composite material obtained in the embodiment and the comparative example was tested using a Malvern laser particle size analyzer. The results are shown in Table 2.
[0101] The powder resistance of the lithium manganese iron phosphate composite materials obtained in the embodiment and the comparative example was tested by an ST2742B powder resistivity tester. The test results are shown in Table 2.
[0102] The lithium manganese iron phosphate prepared in the embodiment and the comparative example was mixed with polyvinylidene fluoride and acetylene black in a mass ratio of 92:4:4, and N-methylpyrrolidone was added to homogenize, and then coated, dried, and rolled to obtain a positive electrode sheet; a polypropylene film was used as a separator, a lithium sheet was used as a negative electrode, and 1 mol / L LiPF6 (DEC:EC=1:1Vol%) was used as an electrolyte. The positive electrode, the separator, and the negative electrode were assembled in sequence to obtain a lithium ion battery. The lithium ion battery was subjected to an electrochemical performance test under the following test conditions: the charge and discharge test was carried out at a room temperature of 25°C at a rate of 0.1C and 1C, respectively, and the results are shown in Table 2.
[0103] Table 1
[0104]
[0105] It can be seen from Table 1 that the sulfur impurity content in the metal-doped modified ammonium manganese iron phosphate precursor, metal-doped modified ferromanganese pyrophosphate, and metal-doped modified lithium manganese iron phosphate prepared in Examples 1 to 3 is effectively controlled to a level of ≤10ppm, which meets the standards of battery-grade positive electrode materials and can avoid the adverse effects of the generation of sulfur-containing byproducts during the cycle on the cycle stability of the battery. At the same time, the ratio of the total molar number of Mn, Fe and doped metal elements to the molar number of P in the metal-doped modified ammonium manganese iron phosphate precursor prepared by the present invention is less than 1, which can make the ammonium manganese iron phosphate precursor itself construct metal defect sites, so that the prepared lithium manganese iron phosphate has a larger lithium ion migration path and space, so as to alleviate the volume expansion effect of the material and improve the electrochemical performance of the lithium manganese iron phosphate.
[0106] Table 2
[0107]
[0108] It can be seen from Table 2 that the compacted density of lithium manganese iron phosphate prepared in Examples 1 to 3 is relatively high, reaching 2.3 g / cm 3 As above, the powder resistance is less than 50Ω·cm, and the 0.1C and 1C first charge and discharge specific capacities, first discharge efficiency and cycle capacity retention rates are significantly increased compared with those of comparative examples 1 to 4, and the powder has excellent rate performance and cycle stability.
[0109] From Comparative Example 1, it can be seen that the conventional method of preparing lithium manganese iron phosphate by directly mixing and grinding the iron source, manganese source and doped metal salt and sintering the lithium source has low compaction density and conductivity and poor electrochemical performance.
[0110] It can be seen from Comparative Example 2 that the ammonium manganese iron phosphate is prepared by co-precipitation method and then used as a precursor to prepare lithium manganese iron phosphate. Since it is impossible to effectively control the molar ratio of Mn, Fe and doped metal elements to P in the precursor and the sulfur impurity content in the finished product, it is not conducive to improving its compaction density, conductivity and electrochemical properties.
[0111] As can be seen from Comparative Example 3, when lithium iron manganese phosphate is directly prepared from a metal-doped modified ammonium iron manganese phosphate precursor, the precursor contains hydrophilic groups, which causes the slurry to agglomerate and over-grind during the grinding process. 50 Much larger than the embodiment. This is because during the sintering process of lithium manganese iron phosphate, nanoparticles are interconnected and grow to form micron-sized large particles, which in turn affects the electrical performance. In addition, since the ammonium in the precursor decomposes to produce ammonia during the sintering process, there are defect sites and excessive porosity in the lithium manganese iron phosphate material, and the rate performance and capacity retention rate of the prepared lithium manganese iron phosphate are lower than those of embodiments 1 to 3.
[0112] It can be seen from Comparative Example 4 that lithium iron manganese phosphate is prepared by mixing conventional NH4FePO4 precursor with manganese sulfate, a lithium source, a dopant, and a carbon source, grinding, spraying, and sintering. This method introduces sulfate ions during grinding, which results in a high sulfur impurity content in the prepared lithium iron manganese phosphate, thereby affecting the powder resistance, discharge capacity, and rate performance of the lithium iron manganese phosphate.
[0113] The above embodiments are preferred experimental methods of the present invention, but the implementation methods of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing modified ammonium manganese ferric phosphate, characterized in that: The following steps are involved: S1. The iron substance is placed in phosphoric acid for reaction, and then an oxidant is added to the reaction, and an alkaline pH regulator containing nitrogen is added to obtain a first system containing ammonium ferric phosphate; S2. Mix manganese sulfate and a doping metal salt, add the mixture to the first system, control the pH value of the system to be 7 to 8.5, and react under an inert atmosphere to obtain the modified ammonium manganese ferric phosphate.
2. The preparation method according to claim 1, characterized in that The chemical formula of the modified ammonium manganese ferric phosphate is NH4Mn x Fe 1-x-m M m PO4, wherein 0<x<1, 0<m<0.1, and M is a doping metal.
3. The preparation method according to claim 1, characterized in that: In step S1, the molar ratio of elemental iron to phosphoric acid is 1:(2-4).
4. The preparation method according to claim 1, characterized in that The pH regulator is one of ammonia water, urea or ammonium carbonate.
5. The preparation method according to claim 1, characterized in that: The metal element of the doped metal salt includes at least one of Ca, Mg, Al, Ti, V, Co, Ni, Cr, Zn, Sn, Mo, Cu, Zr, Nb, Ta, Y, Ce, W, Sc or Ga.
6. A modified ammonium manganese ferric phosphate, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 5.
7. The modified ammonium manganese ferric phosphate according to claim 6, characterized in that: The ratio of the total molar number of manganese, iron and doping metal to the molar number of P in the modified ammonium manganese ferric phosphate is less than 1.
8. A modified manganese ferropyrophosphate, characterized in that: The modified manganese ferropyrophosphate is prepared by calcining the modified ammonium manganese ferrophosphate according to claim 6 or 7 in an inert atmosphere.
9. A modified lithium manganese iron phosphate, characterized in that: The modified lithium manganese iron phosphate is prepared from the modified manganese iron pyrophosphate described in claim 8.
10. A battery, characterized in that: Including the modified lithium manganese iron phosphate as described in claim 9.
Citation Information
Cited By
Preparation of regular triangular flaky ammonium manganese ferric phosphate precursor material
CN120717434A